Monitoramento de 24 horas do desempenho de reator aeróbio de leito fluidizado trifásico na remoção de amônio num sistema de recirculação para produção de tilápia - Sanchez, Ivan A.; Matsumoto, Tsunao [UNESP] (Univ Antioquia, Fac Ciencias Agrarias, 2011)
O objetivo deste trabalho foi monitorar o desempenho de remoção de nitrogênio amoniacal no tratamento das águas residuárias da produção intensiva de tilápia nilótica em sistema com recirculação de água. O sistema foi constituído por um sedimentador convencional e um reator aeróbio de leito fluidizado trifásico com circulação, operados com tempos de detenção hidráulica de 176.4 e 11.9 minutos respectivamente. O meio suporte utilizado no reator foi o carvão ativado granular com densidade aparente de 1.64 g/cm3 e tamanho efetivo de 0.34 mm; a concentração do meio suporte no reator foi mantida constante em 80 g/L. A eficiência média de remoção do nitrogênio amoniacal total foi de 41.2%. O sistema avaliado é uma alternativa efetiva para o reuso da água em sistemas de recirculação para aqüicultura. Embora a variabilidade das concentrações do nitrogênio amoniacal afluente cujo valor médio foi de 0.136 mg/L, o efluente do reator conservou as características de qualidade da água estáveis, com concentrações médias de nitrogênio amoniacal de 0.079 mg/L e do oxigênio dissolvido de 6.70 mg/L, recomendáveis para a criação dos peixes e nas faixas de valores permitidos pela legislação Brasileira (Resolução CONAMA No. 357 de março 5 de 2005) para lançamento de efluentes finais nos corpos de água receptores.

The main objective of this study was to evaluate the ammonia removal efficiency in the wastewater treatment system of an intensive tilapia laboratory production system with water recirculation. The system comprised of a conventional sedimentation basin and an aerobic three-phase fluidized-bed reactor with circulation, operated at hydraulic detention times of 176.4 and 11.9 minutes respectively. Granular activated carbon was used as carrier with apparent density of 1.64 g/cm(3) and effective size of 0.34 mm; the carrier concentration into the reactor was maintained constant at 80 g/L. Mean removal efficiency of total ammonia nitrogen was 41.2%. The evaluated system is an effective option for water reuse in aquaculture recirculating systems. In spite of ammonium nitrogen concentration variability which average value was 0.136 mg/L, the reactor influent maintained water quality characteristics in stable conditions, with average concentrations of ammonia nitrogen of 0.079 mg/L and dissolved oxygen concentration of 6.70 mg/L, recommended for fish culture and within the permitted values by the Brazilian legislation (CONAMA Resolution No. 357 of march 5 of 2005) for the disposal of final effluent in receiving water bodies.

The main objective of this study was to evaluate the ammonia removal efficiency in the wastewater treatment system of an intensive tilapia laboratory production system with water recirculation. The system comprised of a conventional sedimentation basin and an aerobic three-phase fluidized-bed reactor with circulation, operated at hydraulic detention times of 176.4 and 11.9 minutes respectively. Granular activated carbon was used as carrier with apparent density of 1.64 g/cm(3) and effective size of 0.34 mm; the carrier concentration into the reactor was maintained constant at 80 g/L. Mean removal efficiency of total ammonia nitrogen was 41.2%. The evaluated system is an effective option for water reuse in aquaculture recirculating systems. In spite of ammonium nitrogen concentration variability which average value was 0.136 mg/L, the reactor influent maintained water quality characteristics in stable conditions, with average concentrations of ammonia nitrogen of 0.079 mg/L and dissolved oxygen concentration of 6.70 mg/L, recommended for fish culture and within the permitted values by the Brazilian legislation (CONAMA Resolution No. 357 of march 5 of 2005) for the disposal of final effluent in receiving water bodies.
Remoción de amonio en un sistema de recirculación de agua para tilapia mediante un reactor aerobio de lecho fluidizado trifásico
Ammonia removal in a water recirculating system for tilapia using an aerobic three-phase fluidized-bed reactor
Keywords: aerobic reactor; biological treatment; intensive fish culture; recirculation systems; three phase fluidized bed